Land Conversion Versus Subak : How Bali’s Face Gradually Changing Throughout History - Ida Ayu Agung Adnyawati (Bali Tourism Journal, 2019)
Land conversion occurs globally as a result of population dynamics, infrastructure and agricultural expansions, as occurring in the island of God, Bali. Apparently, the land shifting phenomenon in Bali is not as simple as it sounds. It creates a complicated situation in which detrimental to the environment that subsequently affects the socio-cultural aspect in the long run. albeit Balinese rice field, with its Subak System, received UNESCO World Heritage title. The title seems unable to halt the conversion entirely. High demand and limited supply of land in Bali are resulting in skyrocketing price of the estate that slowly pushes the community to liquidate their essential asset. Every year, the horticultural industry is shrinking bit by bit and transforming into real estate. Once an area is transmuted into a residential property or tourism destination, its neighbourhood would be most likely to experience a similar way. As the land composition is changing, migration would follow and boost the conversion process. Though Government is strictly regulating about land conversion through Law Number 41 of 2009 and Law Number 26 of 2007, yet society consciousness plays a vital role to determine whether Bali ricefield with its Subak would survive in the future.